ANALISIS PERMASALAHAN PUSAT INFORMASI KONSELING REMAJA DALAM MEWUJUDKAN MASYARAKAT BERWAWASAN KEPENDUDUKAN - Dini Rakhmawati; Suwarno Widodo; Mujiyono Mujiyono (Universitas Muria Kudus, 2017)
Population-oriented life behavior is the norm / value adopted in life and is expected to be a character for every individual in society. Population-based life behavior is the support of population-oriented development. This research uses qualitative research design. Qualitative research is descriptive research and tend to use analysis. Theoretical basis is used as a guide to focus the research in accordance with the facts in the field. The study involved nine PIK R representing nine sub-districts of sixteen sub-districts in Semarang. Based on observation, interviews, and documentation. Some problems that arise in the management of PIK R to realize population-oriented society, among others, the absence of mentoring from the service, no document guidance to be followed and completed in PIK R, uneven distribution of activity funds, lack of support from the community, difficulties in regeneration, IEC (communication, information and education) services on reproductive health have not run smoothly due to limited personnel and facilities.